Fort-Dauphin beach sands, south Madagascar: natural radionuclides and mineralogical studies - Van, Hao Duong; Lantoarindriaka, Alinanja; Piestrzyński, Adam; Trinh, Phan Trong (Vietnam Journal of Earth Sciences, 2020)
The Fort-Dauphin beach sand placer occurs as black sands on the East-South of Madagascar. The placer contributes 2/3 of the total heavy mineral resources of this country. The major minerals of the deposit are monazite, zircon, quartz, garnet, spinel, sillimanite as non-refractory minerals; ilmenite, anatase, rutile, titanite, leucoxene, pseudorutile and as a refractory one. The average concentration of the ilmenite, monazite, zircon and other minerals is 66.72%, 2.3%, 2.8%, and 28.18% respectively. Ilmenite contains 63 wt.% of TiO2, Zircon - 44 wt.% of ZrO2, Monazite contains 53 wt.% of oxide rare earth elements (REE) and up to 2 wt.% of UO2 and 9 wt.% of ThO2. The total REE in the studied samples was observed high concentration up to 16000ppm and a high ratio of Σ LREE/Σ HREE>31. The principal natural radionuclide in this placer is 232Th with the concentration of 232Th from 2710 to 6000 ppm, 3620 ppm on average while for the 238U from 124 to 340 ppm, 237 ppm on average which are higher than the average of their in Earth’s crust 360 and 70 times respectively.